The acetabulum in healed Legg–Calvé–Perthes disease is cranially retroverted and associated with global reduction of femoral head coverage: a matched-cohort study. Issue 1 (7th February 2020) - Maranho, Daniel A; Ferrer, Mariana; Kalish, Leslie A; Hovater, Whitney; Novais, Eduardo N
Abstract: To evaluate the acetabular morphology in healed Legg–Calvé–Perthes disease after skeletal maturity using computed tomography (CT) scan and to compare with matched controls. We identified 33 (37 hips) patients with healed Legg–Calvé–Perthes disease and closed triradiate cartilage who underwent pelvic CT scan. Each patient was matched based on sex, age and side to a subject with no history of hip disease who had undergone pelvic CT evaluation because of abdominal pain. Both cohorts had 23 (70%) males and mean age of 16.4–16.5 ± 3.6 years. Two independent readers assessed lateral center-edge angle (LCEA), acetabular inclination angle (IA), acetabular depth-width ratio (ADR), acetabular version 10 mm below the dome (cranial) and at the acetabular center and anterior (AASA) and posterior acetabular sector angles (PASA). All measurements had good to excellent interobserver agreement (intraclass coefficients ≥ 0.87). The hips in the Legg–Calvé–Perthes disease cohort had a smaller mean ± standard deviation (SD) superior, anterior and posterior acetabular coverage as assessed by LCEA (13.2° ± 10.7° versus 28.2° ± 3.4°; P  < 0.0001), IA (11.6° ± 6.7° versus 3.5° ± 2.8°; P  < 0.0001), AASA (52.4° ± 9.5° versus 59.3° ± 5.0°; P  = 0.001) and PASA (79.3° ± 5.9° versus 92.3° ± 5.5°; P  < 0.0001) compared with controls. The acetabulum was shallower (ADR 287 ± 45 versus 323 ± 28; P  = 0.0002) and the acetabular version was decreased cranially (0.4°±9.2° versus 8.2°±6.8°; P  = 0.0002) and at the acetabular center (13.7°±5.1° versus 17.2° ±3.8°; P  = 0.004) in Legg–Calvé–Perthes disease hips. After skeletal maturity, hips with healed Legg–Calvé–Perthes disease have shallower and more cranially retroverted acetabula, with globally reduced coverage of the femoral head compared with age-, sex- and side-matched control hips.